VD_FINDINFO HC / 2015 / 858 vom 8. Oktober 2015 - VD Tribunal cantonal (2015)
DÉCISION SUR FRAIS, TRANSACTION EXTRAJUDICIAIRE | 105 CPC (CH), 109 al. 1 CPC (CH), 241 al. 2 CPC (CH), 241 al. 3 CPC (CH), 65 al. 2 TFJC (2010), 67 al. 2 TFJC (2010)